Effects of musical cadence in the acute physiologic adaptations to head-out aquatic exercises - Barbosa, Tiago M. (2020)
The purpose of this study was to analyze the relationships between musical cadence and the physiologic adaptations to basic head-out aquatic exercises. Fifteen young and clinically healthy women performed, immersed to the breast, a cardiovascular aquatic exercise called the "rocking horse." The study design included an intermittent and progressive protocol starting at a 90 b.min(-1) rhythm and increasing every 6 minutes, by 15 b.min(-1), up to 195 b.min(-1) or exhaustion. The rating of perceived effort (RPE) at the maximal heart rate achieved during each bout (HRmax), the percentage of the maximal theoretical heart rate estimated (%HRmax), and the blood lactate concentration ([La-]) were evaluated. The musical cadence was also calculated at 4 mmol.L(-1) of blood lactate (R4), the RPE at R4 (RPE@R4), the HR at R4 (HR@R4), and the %HRmax at R4 (%HRmax@R4). Strong relationships were verified between the musical cadence and the RPE (R2 = 0.85; p < 0.01), the HRmax (R2 = 0.66; p < 0.01), the %HRmax (R = 0.61; p < 0.01), and the [La-] (R2 = 0.54; p < 0.01). The R4 was 148.13 +/- 17.53 b.min, the RPE@R4 was 14.53 +/- 2.53, the HR@R4 was 169.33 +/- 12.06 b.min, and the %HRmax@R4 was 85.53 +/- 5.72%. The main conclusion is that increasing musical cadence created an increase in the physiologic response. Therefore, instructors must choose musical cadences according to the goals of the session they are conducting to achieve the desired intensity.